PρTx properties of binary R134a/R245fa system. (August 2019) - Qi, Yingxia; Yang, Haifeng; Zhang, Can
Highlights: The mixed refrigerants (R134a + R245fa) as a new alternative ORC refrigerant. PVTx experimental data of (R134a + R245fa) mixtures at six mass fractions. Virial equations of state are fitted. Abstract: The gaseous PVTx properties of 1, 1, 1, 2-tetrafluoroethane (R134a) + 1, 1, 1, 3, 3-pentafluoropropane (R245fa) mixtures were measured at pressures from 124 to 650 kPa, temperatures from 300.15 to 335.15 K and the compositions of R134a from 0.30 to 0.55 mass fraction using the Burnett isothermal expansion method. The uncertainty of temperature measurement was estimated to be within ±10 mK temperature, the pressure was within ±4 kPa, the mass fraction was within ±0.3%, and the compression factor was within ±0.06%. Based on the experimental PVTx property data, the densities and gas virial equation of the mixed refrigerants at the different temperatures and pressures were fitted. It provided detailed data for the further research on the performance of the Organic Rankine Cycle adopting the new alternative refrigerant.